Respostas

2014-07-30T20:31:24-03:00


a)f(4)= 4.4+1=17

b)f(-2)=4.(-2)+1=-7

c)f(-1)=4.(-1)+1=-3 + f(0)=4.0+1=1 - f(11)4.11+1=45

              -3+1-45=-47

d)2.f(3)=4.3+1=13 - f(-3)=4.(-3)+1=-11

       2.13+11=37   

1 3 1
A melhor resposta!
2014-07-30T20:31:44-03:00
A) f(4)= 4x4+1
   f(4)= 16+1
    f(4)= 17
b) f (-2) = 4.(-2)+1
   f (-2) = -8+1
              -7
c)  f(-1) = 4.(-1)+1
     f(-1) = -4+1
                -3
f(0)= 4.0+1
         0+1
          1
f(11)= 4.11+1
           44 + 1
              45
f(-1)+f(0)+f(11)=
-3 + 1 + 45
43

D) f(3) = 4.3+1
             13
f(-3)= 4.(-3)+1
         -11
2.f(3)-f(-3)=
2.13 - (-11)
37
1 5 1